Writing up or writing off crimes of domestic violence? A transitivity analysis of police reports - Canning, Patricia (Language and Law / Linguagem e Direito, 2022)
Between March 2019 and March 2020 in England and Wales (excluding Greater Manchester), there were 1,288,018 recorded incidents of domestic violence (DV, otherwise known as ‘domestic abuse’ or ‘DA’), an increase of 4.2% (51,404 incidents ) on the previous year (Office for National Statistics (ONS)). Only 56% of these were classified by police as ‘crimes’ (ONS). Additionally, despite the annual rise of DV the charging rate of suspects fell in 2019–2020 by 20.5% (Crown Prosecution Service data (CPS)). This raises two primary questions: 1) why are almost half of reported DV incidents not considered ‘crimes’? and 2) in spite of rising numbers of incidents, why do prosecutions continue to fall? These questions are central to this paper. A possible factor influencing attrition rates concerns the language used by police officers to record DV incidents. This paper then, explores whether the linguistic choices made by police officers on judicial reports of DV reflect implicit attitudinal biases, that in turn, can potentially pre-empt out-of-court case disposals. If so, this may also go some way to explaining the gap between cases reported as DV crimes and cases recorded as such. The dataset under analysis comes from a corpus of 13 police-authored DV cases sent to prosecutors for charging decisions in one calendar month in 2010 (for more detail about the corpus, see Lea and Lynn 2012). All 13 cases were returned with a ‘simple caution’ outcome, which means that none progressed to prosecution. The analysis of the reports is carried out using the model of transitivity (Berry 1975, Halliday 1994) to identify participant roles, actions, and circumstances as well as their syntactic distribution. The analysis shows that officers’ lexical and syntactic choices yield patterns of agency that downplay suspects’ culpability on the one hand, and background victims on the other. The paper concludes by arguing that how police present agency, participant roles, and circumstantial elements in reports to prosecutors can encode a ‘preferred outcome’ resulting in more lenient charging decisions.